2021
DOI: 10.5005/jp-journals-10071-24016
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-virological Profile, Intensive Care Needs, and Outcome of Infants with Acute Viral Bronchiolitis: A Prospective Observational Study

Abstract: Objectives The objective of the study was to describe the clinico-virological profile, treatment details, intensive care needs, and outcome of infants with acute viral bronchiolitis (AVB). Methodology In this prospective observational study, 173 infants with AVB admitted to the pediatric emergency room and pediatric intensive care unit (PICU) of a tertiary care teaching hospital in North India during November 2019 to February 2020 were enrolled. The data collection incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
1
2
2
Order By: Relevance
“…During the hospitalization, none of our patients was diagnosed with AKI. This, in addition to the presence of only one report describing an association between AKI and bronchiolitis [ 8 ], further confirms our meaning that AKI, especially in its milder forms, is often under-recognized in children [ 4 7 ].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…During the hospitalization, none of our patients was diagnosed with AKI. This, in addition to the presence of only one report describing an association between AKI and bronchiolitis [ 8 ], further confirms our meaning that AKI, especially in its milder forms, is often under-recognized in children [ 4 7 ].…”
Section: Discussionsupporting
confidence: 87%
“…Despite the non-PICU setting of the study, our data confirmed that a considerable percentage (about 11%) of patients with viral bronchiolitis may develop AKI. This prevalence is higher than the one (7.5%) reported by Angurana et al [ 8 ], which —unlikely— did not provide the methods to diagnose AKI nor the different stages of the disease. Probably, only the more severe AKI cases were accounted in such paper [ 8 ].…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations